A multicomponent reaction-initiated synthesis of imidazopyridine-fused isoquinolinones - Ashutosh Nath; John Mark Awad; Wei Zhang (Beilstein Journal of Organic Chemistry)
A new synthetic route initiated with Groebke–Blackburn–Bienaymé (GBB) followed by N-acylation, intramolecular Diels–Alder (IMDA), and dehydrative re-aromatization reactions for the synthesis of imidazopyridine-fused isoquinolinones is developed. Gaussian computation analysis on the effect of the substitution groups for the IMDA reaction is performed to understand the reaction mechanism.